Genetic composition of green sea turtles (Chelonia mydas) at coastal feeding areas of Uruguay - Prosdocimi, Laura; Vilaca, Sibelle Torres; Naro-Maciel, Eugenia; Caraccio, Maria N.; Formia, Angela; Vélez-Rubio, Gabriela M. (Frontiers in Amphibian and Reptile Science, 2024)
The highly migratory and marine nature of species such as green sea turtles (Chelonia mydas) may hinder understanding of basic life history and impact ensuing management and conservation applications across their full range. To elucidate the linkages between juvenile green turtles foraging in coastal waters of Uruguay in the Southwestern Atlantic Ocean to their future nesting or feeding grounds, this study investigated their genetic composition . A total of 201 tissue samples were collected from turtles that had stranded or were intentionally captured for scientific research along the Uruguayan coast (ca. 33°–35°S) during two sampling periods (2003–2005 and 2009–2014). Samples were pooled for analysis. Twelve mitochondrial control region haplotypes and ten subhaplotypes were identified, all of which had been previously detected at Atlantic or Caribbean nesting beaches. Mixed Stock Analysis revealed that most turtles traced to the Ascension Island rookery, representing a substantial connection to the remote mid-Atlantic island thousands of kilometers distant. Other nesting areas, such as Guinea Bissau in Africa and Trindade Island in Brazil, represented less significant sources. There was no significant temporal or spatial genetic structure within Uruguayan waters, suggesting dispersion along this coast. Despite the geographic distance from the nesting beach, the significant connection to the Ascension Island rookery underscores the importance of considering rookery population size and ocean current influences in understanding source contributions. These findings emphasize the need for conservation efforts, including the maintenance of existing protected areas and the creation of new ones, to ensure the long-term conservation of green turtles connected to various nesting colonies and feeding grounds.